PERMASALAHAN RESTORASI DAN KONSERVASI PENERAPANNYA PADA CANDI MORANGAN, YOGYAKARTA - Chawari, Muhammad (BRIN, 2005)
In the effort of preservation (including maintenance) and utilization (including management), the main activities are in the form of conservation which includes restoration. So restoration is one form of activity in conservation, in addition to maintenance, preservation, reconstruction, and adaptation. In order to restore the Morangan Temple, the first thing to do is reconstruction on paper. This reconstruction is to see how far the restoration of the Morangan Temple can be done.